2020
DOI: 10.1021/acsami.9b21215
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–Ellagic Acid Nanohybrid for Mitigating Rotenone-induced Oxidative Stress

Abstract: Antioxidants derived from nature, such as ellagic acid (EA), demonstrated high potency to mitigate neuronal oxidative stress and related pathologies, including Parkinson’s disease. However, the application of EA is limited due to its toxicity at moderate doses and poor solubility, cellular permeability, and bioavailability. Here, we introduce a sustainably resourced, green nanoencasement strategy to overcome the limitations of EA and derive synergistic effects to prevent oxidative stress in neuronal cells. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 78 publications
(142 reference statements)
0
32
0
Order By: Relevance
“…However, EA treatment prior to MPTP administration significantly increased the GSH level and decreased the MDA level, again suggesting the antioxidant function of EA. In several studies, EA has been widely reported to exert free radical scavenging and potent antioxidant activity by scavenging ROS and restoring the activity of cellular antioxidant enzymes [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, EA treatment prior to MPTP administration significantly increased the GSH level and decreased the MDA level, again suggesting the antioxidant function of EA. In several studies, EA has been widely reported to exert free radical scavenging and potent antioxidant activity by scavenging ROS and restoring the activity of cellular antioxidant enzymes [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The peak intensity at 1026 cm −1 seen in pure powders was reduced with bead formation due to perturbation by calcium and weakening in the bonds 36 . The chitosan spectrum used in this study showed an absorption peak marked at 1620 and 1518 cm −1 (LC) and 1648 and 1590 cm −1 (HC) attributed to the carbonyl stretching of amide (amide I band) and bending vibrations of NH (amide II) and at 1456 cm −1 corresponding to amide III vibrations 38,39 . The characteristic peaks of chitosan that appeared at 1590 cm −1 were overlapping with alginate; the peak of amino groups (NH 2 ) of chitosan at 1150 cm −1 showed itself as a shouldering peak in the chitosan‐coated beads with lower intensity due to a partial covalent bonding between calcium and oxygen atoms present in the chitosan structure 40 …”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, the nanoformulation outperformed free EA in several activities: amelioration of apoptosis, inhibition of Cyto-C release, activation of caspases, regulation of P53, Bax, and Bcl-2 protein expression, and protection against DNA damage. Moreover, the EA and chitosan-coated combination mitigated rotenone-induced ROS overproduction and reduced cytotoxicity [355]. The antioxidant and antiaging properties of CA-loaded nanotransfersomes were found to enhance cell viability, reduce intracellular ROS generation, attenuate lipid peroxidation, and modulate MMP expression [350].…”
Section: Neuroprotective Role Of Phytochemical Nanoformulationmentioning
confidence: 99%